THE DIMENSION OF EMPLOYER BRANDING: ATTRACTING TALENTED EMPLOYEES TO LEVERAGE ORGANIZATIONAL COMPETITIVENESS - Purusottama, Ambara; Ardianto, Ari (Universitas Brawijaya, Indonesia, 2019)
The challenge to meet the fulfillmentofthe workforce needs in Indonesia in the near future makes organizations immediately improve and use employer branding as an instrument of organizational competitiveness in